P060: Imaging practices of emergency physicians for low risk non-traumatic low back pain. (15th May 2017) - Hiranandani, R.; MacKenzie, M.; Wang, D.; Lang, E.
Abstract : Introduction: Included in the first list of recommendations from the Choosing Wisely Canada (CW) Emergency Medicine (EM) group was to avoid ordering lumbosacral radiographs for patients with non-traumatic low back pain (LBP) in the absence of red flags. It has been suggested that these lumbosacral radiographs lead to unnecessary ionizing radiation and increase emergency department (ED) wait times without improving patient outcomes. This study evaluates lumbosacral imaging practices of emergency physicians (EPs) in four urban EDs.Methods: Data was retrospectively collected from patients, ages 18-60 and CTAS codes 2-5, who presented with non-traumatic LBP from April 1, 2014 to March 31, 2016 to four urban EDs. The time frame included both pre- and post-CW recommendation. Patients considered high risk, specifically with PTT >40 s or INR >1.2 s, neurology/neurosurgery/spine consults, admission to hospital, and history of cancer, were excluded. The primary outcome was to establish lumbosacral radiograph usage rates for non-traumatic LBP. The secondary outcome was to identify factors that influenced lumbosacral spine imaging. Factors analyzed included patient age, patient sex, ED wait times, physician age, physician experience, and physician sex. Statistical significance was determined by chi-squared analysis.Results: The data from 3140 low-risk patients showed that 16.5% of the patients received lumbosacral radiographs. Physician variation in X-ray ordering was 0% to 85.7% (IQR 4.6 to 25%). There was a significant difference between the X-rays ordered at each site (site 1 (23.1%)>site 2 (17.2%)>site 3 (14.9%)>site 4 (11.3%), p<0.001). CCFP-EM licensed physicians (17.9%) ordered more X-rays compared to licensed physicians (13.7%, p<0.001). Time of presentation, physician sex, and patient sex did not affect the imaging practices. There was a trend towards decreased ordering of X-rays (17.6% vs. 15.1%, p=0.06) post-CW recommendation.Conclusion: Considerable variation exists in the ordering practices of Calgary EPs; however, on average they are choosing wisely in terms of ordering imaging for non-traumatic LBP.